Comparing the adverse outcomes of left atrial appendage occlusion in patients with diabetes. (14th October 2021) - Gill, J
Abstract: Introduction: In patients with atrial fibrillation, it is estimated that greater than 90 percent of left atrial thrombi are located in the left atrial appendage. Multiple percutaneously implanted devices have been approved worldwide for left atrial appendage occlusion (LAAO) to reduce stroke risk in patients not suitable for long-term oral anticoagulation. Device implantation has been associated with a high success rate and low risk for peri-procedural complications. However, as the prevalence of diabetes continues to rise, there is a considerable need to establish peri-procedural risk in these patients. Purpose: This study aimed to evaluate and compare the in-hospital outcomes of LAAO in patients with and without diabetes. Methods: We performed a retrospective cross-sectional analysis using the 2018 National Inpatient Sample. All patients aged 18 years and older with atrial fibrillation and LAAO-related hospitalizations were included in this study. To mitigate selection bias and control for patient and institutional imbalances, propensity scoring method was used to select matched sample between patients with diabetes and patients without diabetes. The scoring was based on a multivariate logistic regression model accounting for age, gender, race, hospital type, hospital region, hospital teaching status, median household income, and medical comorbidities. Using an 8-to-1-digit match, we paired each admission in the diabetes group with one admission without diabetes. Results: We identified a total of 3572 patients admitted for LAAO; 1298 of these patients had comorbid diabetes. Diabetics did not have a higher risk of in-hospital mortality with LAAO (0.2% vs 0.3%, p=0.620). The risk for 17 out of the 18 identified peri-procedural complications was similar in patients with and without diabetes. However, diabetes was associated with an increased risk of acute kidney injury (Adjusted OR 1.75; 95% CI 1.05–2.93, p=0.03). Interestingly, 0 endocarditis events were captured in both groups, indicating that this complication is only seen in long-term follow-up and had a peri-procedural risk of 0%. Conclusion: As the use of implantable LAAO devices increases worldwide, clinicians should be cognizant of the increased risk for peri-procedural acute kidney injury in diabetics. Patients with diabetes often have diabetes-induced chronic kidney disease with susceptibility to acute injury. Therefore, volume status should be closely monitored in the peri-procedural period to mitigate further damage to the kidneys in these patients. Funding Acknowledgement: Type of funding sources: None.